The Impact of Psychological Biases on the Decision-making of the Individual Albanian Investor - Dervishaj, Blerina; Xhaferi, Teftjola (International Journal of Economics and Financial Issues, 2020)
The study aims to measure the impact of psychological biases on financial decisions of the albanian individual investor. The paper uses primary data provided through structured interviews with 180 individual investors and one semi-structured interview with an expert of the financial market in Albania. Exploratory Financial Analysis, Cronbach alpha test and descriptive analysis are used through R- software. The analysis and its results conclude a significant presence of psychological biases on the albanian individual investor behaviour. As there is too little research done on this field in Albania, the study informs of the presence of these biases and tries to explain their impact not only on the previous crisis the country has experienced, but also on the current situation of the financial market in the country. Keywords: psychological bias, individual investitor, financial decision-making, financial market. JEL Classifications: G, G4, G41 DOI: https://doi.org/10.32479/ijefi.9488